2022
DOI: 10.1186/s12870-022-03946-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative plastomes and phylogenetic analysis of seven Korean endemic Saussurea (Asteraceae)

Abstract: Background Saussurea is one of the most species-rich genera in the Cardueae, Asteraceae. There are approximately 40 Saussurea species distributed in Korea, with nearly 40% of them endemics. Infrageneric relationships remain uncertain due to insufficient resolutions and low statistical support. In this study, we sequenced the plastid genomes of five Korean endemic Saussurea (S. albifolia, S. calcicola, S. diamantica, S. grandicapitula, and S. seoulensis), and comparative analyses including two o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 72 publications
2
6
0
Order By: Relevance
“…The IRb/SSC and IRa/LSC boundary shifts between the species commonly included the ycf 1 and rps 19 pseudogenes, respectively. Overall, our results demonstrated that the conservation pattern of plastomes is similar to those of other Saussurea species (Zhang et al 2019 ; Yun and Kim 2022 ).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The IRb/SSC and IRa/LSC boundary shifts between the species commonly included the ycf 1 and rps 19 pseudogenes, respectively. Overall, our results demonstrated that the conservation pattern of plastomes is similar to those of other Saussurea species (Zhang et al 2019 ; Yun and Kim 2022 ).…”
Section: Discussionsupporting
confidence: 84%
“…Many studies have reported the use of chloroplast SSR markers with high polymorphisms in Saussurea (Shen et al 2020 ; Yun and Kim 2022 ). In previous studies, the genetic variability in snow lotus species has been investigated using genetic markers of the nuclear genome (Yuan et al 2009 ; Wei et al 2017 ; Nyamgerel et al 2023 ), but they revealed lower genetic diversity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is limited evidence of DNA transfer between organellar genomes within the Asteraceae family reported in the literature. BLAST search results indicated that the inserted sequences showed a high degree of similarity to mitochondrial DNA sequences from Chrysanthemum , Diplostephium , Lactuca , Helianthus , and Paraprenanthes [ 42 ]. In this study, we conducted an analysis of the homologous sequences between the mitogenomes and plastomes of two chamomile species.…”
Section: Discussionmentioning
confidence: 99%
“…The pairwise sequence divergence was calculated based on the Kimura 2-parameter method ( Kimura, 1980 ) using MEGA11 ( Tamura et al., 2021 ). According to earlier studies, we sequenced the entire plastome (e.g., Kim et al., 2019 ; Cho et al., 2020 ; Yang et al., 2021 ; Yun and Kim, 2022 ). An Illumina paired-end (PE) genomic library was constructed and sequenced using the Illumina HiSeq platform (Illumina, Inc., San Diego, CA, USA) at Macrogen Corporation (Seoul, Korea).…”
Section: Methodsmentioning
confidence: 99%